2021
DOI: 10.3390/cells10071767
|View full text |Cite
|
Sign up to set email alerts
|

Renin–Angiotensin–Aldosterone System and Immunomodulation: A State-of-the-Art Review

Abstract: The renin–angiotensin system (RAS) has long been described in the field of cardiovascular physiology as the main player in blood pressure homeostasis. However, other effects have since been described, and include proliferation, fibrosis, and inflammation. To illustrate the immunomodulatory properties of the RAS, we chose three distinct fields in which RAS may play a critical role and be the subject of specific treatments. In oncology, RAS hyperactivation has been associated with tumor migration, survival, cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 187 publications
(236 reference statements)
0
48
0
2
Order By: Relevance
“…Renin is an enzyme secreted by kidney juxtaglomerular cells that supply blood to the glomeruli and is regulated by pressure reduction in the afferent arterioles, neural stimulation, and feedback in the distal tubules [ 32 ]. Renin is involved in the conversion of angiotensinogen (synthesis in the liver) into angiotensin I, which is converted by the angiotensin-converting enzyme (ACE) (secreted in the lungs) into angiotensin II, which has a strong vasoconstrictive effect [ 29 , 33 ]. Next, angiotensin II stimulates the cortex of the adrenal glands to secrete aldosterone, which, by retaining sodium, maintains the correct intravascular volume.…”
Section: Electrolyte Balancementioning
confidence: 99%
“…Renin is an enzyme secreted by kidney juxtaglomerular cells that supply blood to the glomeruli and is regulated by pressure reduction in the afferent arterioles, neural stimulation, and feedback in the distal tubules [ 32 ]. Renin is involved in the conversion of angiotensinogen (synthesis in the liver) into angiotensin I, which is converted by the angiotensin-converting enzyme (ACE) (secreted in the lungs) into angiotensin II, which has a strong vasoconstrictive effect [ 29 , 33 ]. Next, angiotensin II stimulates the cortex of the adrenal glands to secrete aldosterone, which, by retaining sodium, maintains the correct intravascular volume.…”
Section: Electrolyte Balancementioning
confidence: 99%
“…The angiotensin converting enzyme-2 (ACE2) serves as a master regulator of the RAS. By metabolizing the vasoconstricting and pro-inflammatory angiotensin II (Ang II), ACE2 generates Ang 1-7, which counteracts the pro-inflammatory and pro-oxidant effects of Ang II ( 11 ). Molecular studies have demonstrated that ACE2 is the SARS-CoV-2 cell entry receptor, through the activation of the viral outer membrane spike protein S by transmembrane protease serine 2 (TMPRSS2) ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…All these effects are primary mediated through the binding of angiotensin II to its type 1 receptor, which belongs to the G protein-coupled receptor superfamily, in blood vessels, kidney, brain and heart ( 25 ). Besides its classical cardiovascular effects, angiotensin II might also exert inflammatory, pro-proliferative and pro-fibrotic effects, involved in oncologic and transplantation pathways ( 26 ).…”
Section: Discussion and Review Of The Different Available Vasopressorsmentioning
confidence: 99%
“…Given its vasopressor activity which allows the restoration of vascular tone and arterial pressure through both venous and arterial constriction, ( 27 ) the interest of angiotensin II administration has been studied in vasodilatory shock and especially in septic shock, since a relative renin-angiotensin system failure has been evidenced in sepsis, illustrated by a relative decrease in angiotensin II plasma levels combined with a decrease in sensitivity to angiotensin II stimulation ( 26 ). Thus, some experimental ( 28 – 30 ) and human studies ( 31 35 ) have shown that angiotensin II administration allowed improvements to arterial pressure and even a catecholamine-sparing effect ( 36 ).…”
Section: Discussion and Review Of The Different Available Vasopressorsmentioning
confidence: 99%